(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The professional skills of a specialist directly affect the quality of the training process, the motivation of athletes and their achievements. The article is devoted to the problem of professional skill of a gymnastics specialist, which is a multi-component category and includes methodological, psychological-pedagogical and communicative competence. In gymnastics, as in a technically complex sport, the success of athletes largely depends on the level of training, which is determined by the professionalism of the coach. The authors emphasize that the coach not only forms the technical skills of gymnasts, but also ensures their psychological stability, motivation and emotional preparation for competitions. The article emphasizes the importance of the methodological competence of a specialist, which determines the effectiveness of planning and implementing the training process, adapting programs to the individual characteristics of athletes, and applying advanced training methods. It also considers psychological and pedagogical competence, which is necessary to create a favorable psychological environment, support athletes in difficult moments, and form their emotional resilience. Particular attention is paid to the communication skills of the coach, which play a key role in interacting with athletes, their parents, and other participants in the training process. The authors analyze modern innovative technologies in gymnastics, including the use of video analysis, digital platforms for monitoring physical indicators, and interactive teaching methods. The results of the study emphasize the need for a comprehensive approach to the development of the professional skills of a gymnastics specialist, which contributes to increasing the effectiveness of athletes’ training, improving their results, and the overall development of gymnastics as a sport.